Overweight and Obese Children's Ability to Report Energy Intake Using Digital Camera Food Records during a 2-Year Study - Åsa Svensson; Maria Waling; Catharina Bäcklund; Christel Larsson (Journal of Nutrition and Metabolism)
The objective was to evaluate overweight and obese children's ability to report reproducible and valid estimates of energy intake (EI) by using digital camera food records (FR) during a 2-year study, compared with objectively measured total energy expenditure (TEE). Seventy-three overweight/obese children, aged 8–12 years at inclusion, kept FR with the help of digital cameras for 16 days in total, on 7 occasions during a 2-year period. On the same days, their TEE was registered with SenseWear Armband (SWA). The children underestimated their EI by −2.8 (2.4) MJ/d on the first assessment occasion (95% CI: −3.3, −2.3). Reporting accuracy did not differ between the 7 assessment occasions (P=0.15). Variables negatively associated with reporting accuracy relative to TEE were increased age (95% CI: −0.07, −0.01) and BMI z-score (95% CI: −0.18, −0.06). Further, reporting accuracy relative to TEE was lower for girls than boys (95% CI: −0.14, −0.01) and on weekdays compared with weekend days (95% CI: −0.08, −0.001). In conclusion, overweight and obese children were able to report their EI using a digital camera FR with good reproducibility over a 2-year period, even though their EI was underestimated compared with objectively measured TEE.